Talent Management Practices and Organizational Performance: Mediation Role of Organizational Commitment - Gautam, Kishor Kumar (Nepalese Journal of Management Science and Research, 2024)
This study aims to assess the influence of talent management (TM) practices on organizational commitment and performance in Nepalese banks located in the Kathmandu Valley. The present study employed a combination of descriptive and quantitative methodologies, with the research focusing on the bank employee as the unit of analysis. To ensure a representative sample, a simple random and stratified sampling technique was employed, resulting in a research sample size of 300 officers and managers of a Nepalese commercial bank. Primary data were collected through the administration of a questionnaire to the target population. Confirmatory factor analysis (CFA), path analysis–and structural equation modeling were employed under a bootstrapping approach. The findings of this study indicate that the implementation of TM practices, such as talent attraction, talent development, and talent retention, has a notable impact on organizational performance. Furthermore, it was observed that organizational commitment plays a mediating role in the relationship between TM practices and organizational performance within the context of the Nepalese bank. Consequently, this research strongly advocates for bank management to embrace and allocate resources towards the adoption of TM practices to enhance organizational commitment and ultimately achieve and sustain high levels of organizational performance.